A Closing Window of Opportunity to Save a Unique Marine Ecosystem - Kleinhaus, Karine; Voolstra, Christian R.; Meibom, Anders; Amitai, Yael; Gildor, Hezi; Fine, Maoz (Frontiers in Marine Science, 2020)
Abstract • Five years in the making, a massive oil spill of 1 million barrels is anticipated to occur shortly in the Red Sea off the coast of Yemen • Emergent action must be taken by the UN and its International Maritime Organization to remove the oil, despite regional political tensions, as a spill during winter will exacerbate the destruction. • With millions of barrels of oil a day passing through the Red Sea, a regional strategy must be drafted for leak prevention and containment that is specific to the Red Sea’s unique ecosystems, unusual water currents, and political landscape.